Protein structure alignment with a dynamic programming algorithm using dihedral angles - Ang, Seok Yan (2009)
In molecular biology, a common question often rises about a gene or protein is whether it is related to any other gene or protein. One of the most widely used approaches to distinguish if they are related is by sequence alignment. However, research has shown that sequence alignment has its limitations, where aligned sequences indicating high similarity may not share similar properties and vice versa.